Comparison of some properties of two structurally similar four component liquid crystalline mixtures. (13th October 2017) - Sarkar, K.; Mukhopadhyay, A.; Garbat, K.; Dabrowski, R.
ABSTRACT: The present work reports the temperature dependence of the dielectric properties of two four component thermotropic liquid crystalline mixtures with same core structure but with different polar functional group i.e., the cyano (‒CN) and isothiocyanato (‒NCS). A comparative study of variation of dielectric permittivities of the two mixtures has been made and their effective molecular dipole moments (μeff ) determined as a function of temperature. Using the data obtained from previous optical studies and data collected from present study, a comparison of the temperature variation of the angle of inclination β of the effective molecular dipole moment with director for both the mesogens could be made. In order to determine the nature of the molecular association in the mesophase, the effective molecular correlation factors (g) have been estimated from measurements of dipole moments of the compounds in solutions.